Cross-Cultural Pragmatics: Analysing Speech Acts in Different Cultures - Usmani, Saima; ALMASHHAM, AMAL (International Journal of Language and Literary Studies, 2024)
Cross-cultural communication entails understanding the nuanced differences in speech acts across diverse cultural contexts. This study aimed to explore these variations, focusing on pragmatic differences and similarities in speech acts among participants from various cultural backgrounds. Employing qualitative methods, communicative scenarios were devised to elicit speech acts, and interactions were recorded for analysis. The participants’ cultural backgrounds were diverse, representing a range of ethnicities, languages, and socio-cultural contexts. Data analysis involved categorizing and comparing speech acts across cultures, identifying patterns, and examining cultural influences on speech act usage. Results indicated significant variations in the frequency, form, and interpretation of speech acts among different cultural groups. Cultural norms, values, and communication styles were found to shape participants’ understanding and enactment of speech acts, highlighting the intricate relationship between language and culture in communication. These findings have important implications for intercultural communication, language education, and international business. Understanding cultural differences in speech act usage can enhance communication effectiveness in diverse settings, fostering mutual understanding and reducing misunderstandings. Overall, this study contributes to the growing body of research on cross-cultural pragmatics, emphasizing the need for culturally sensitive approaches to communication in an increasingly globalized world.